2015
DOI: 10.1161/circresaha.117.306340
|View full text |Cite
|
Sign up to set email alerts
|

Determinants and Outcomes of Accelerated Arteriosclerosis

Abstract: Rationale: The role of circulating antibodies in addition to traditional cardiovascular risk factors in the development of accelerated arteriosclerosis and their long-term clinical consequences have not been demonstrated. Objective: We investigated the role of circulating antibodies in accelerated arteriosclerosis and the role of immune-associated arteriosclerosis in graft and patient survival and the occurrence … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
54
0
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 50 publications
(55 citation statements)
references
References 52 publications
0
54
0
1
Order By: Relevance
“…Note that the extent of i‐IFTA is not analogous to the Banff total inflammation score, the latter representing the sum of inflammation in scarred and nonscarred areas of the cortex. Consequently, it was decided to modify the Banff 2007 criteria by adding a statement (Table 3, category 4), reflecting findings that lesions of transplant arteriopathy may represent chronic active ABMR 42 as well as TCMR—also shown in experimental studies 43—and that chronic active TCMR may also be manifest in the tubulointerstitial compartment.…”
Section: Chronic Active Tcmr and Interstitial Inflammation In Areas Omentioning
confidence: 99%
“…Note that the extent of i‐IFTA is not analogous to the Banff total inflammation score, the latter representing the sum of inflammation in scarred and nonscarred areas of the cortex. Consequently, it was decided to modify the Banff 2007 criteria by adding a statement (Table 3, category 4), reflecting findings that lesions of transplant arteriopathy may represent chronic active ABMR 42 as well as TCMR—also shown in experimental studies 43—and that chronic active TCMR may also be manifest in the tubulointerstitial compartment.…”
Section: Chronic Active Tcmr and Interstitial Inflammation In Areas Omentioning
confidence: 99%
“…One of the forms of sHLA-I consists of sHLA HC monomers associated with β2m; the other has a molecular weight indicative of HLA antigen/antibody complexes. Rhynes, et al [134] also noticed the presence of this sHLA-Iin one of the patients who had rejected the allograft. The molecular weight of one of the isolated sHLA forms was higher than the usual molecular weight (near 1,000,000 daltons), which was attributed to the presence of sHLA/antibody complexes in allograft recipients.…”
Section: Donor Specific Shla In Allograft Recipientsmentioning
confidence: 88%
“…Levels of sHLA in allograft recipients that increased, post-transplantation, from a detectable pre-transplant level, and the persistence of sHLA at a high level as long as the liver allograft functioned confirmed the post-transplantation shedding of sHLA by allografts. Rhynes, et al [134] observed that the serum sHLA levels were low pre-transplant but increased substantially during the initial 10 days post-transplantation in liver (n = 9) and heart (n = 12) allograft recipients. In renal transplant patients, the increase in sHLA-I was noticed prior to or during 16 of 20 (80%) biopsy-proven rejections and in 9 of 11 (83%) after episodes of infection (bacterial, viral, and fungal).…”
Section: Donor Specific Shla In Allograft Recipientsmentioning
confidence: 99%
“…DSA may also promote arteriosclerosis, as judged by progression of severity in allografts from patients with DSA. Loupy et al recently suggested that circulating antibodies are major determinants of severe arteriosclerosis and major adverse cardiovascular events, independent of traditional cardiovascular risk factors [41].…”
Section: Characteristic Histological Manifestations Of Chronic Abmrmentioning
confidence: 99%